(untitled) (Journal of Bio-Science, 2009)
The purpose of the present study was to estimate the effect of phenotypic characteristics on the performances of bulls at three AI centres/stations (CCBSDF, Savar, RDCIF, Rajabarihat and District AI centres, Rajshahi). A total 71 bulls were studied for phenotypic parameters, viz., body weight, body condition score, scrotal circumference (SC), libido score and time required between two ejaculates during 1993 to 2002. The information on the phenotypic parameters was obtained by interviewing the semen collectors in respective AI centers, reading the AI bull resister as well as examining and observing the bull during semen collection. The bulls were classified according to genetic composition viz., Group I: 100% Friesian, Group II: 100% Sahiwal, Group III: 75% Friesian? 25% Local, Group IV: 50% Sahiwa l?50% Friesian, Group V: 50% Friesian ? 50% Local and Group VI: 100% Local. In general, the average body weight, body condition score, scrotal circumference (SC), libido score and time required between two ejaculates were 572 ? 124 kg, 3.2 ? 0.5 (Score:1-5), 36.3 ? 1.9cm, 3.3 ? 0.6 (Score:1-5) and 7.1 ? 2.3 minutes, respectively. Individual bull had significant effect on phenotypic characteristics in six genetic groups. The overall better performance of phenotypic parameter was observed in bull Id #: 0065 for Friesian breed, 163 for 100% Sahiwal breed, 7811 for 75% Friesian ?25% Local, 5156 for 50% Sahiwal?50% Friesian, 8224 for 50% Friesian ? 50% Local and 40248 for 100% Local breed. Therefore, phenotypic characteristics has clearly influenced on bull performances of Artificial Insemination (AI) programme in Bangladesh. Key words: Phenotypic characteristics, Individual bull and AI. DOI: http://dx.doi.org/10.3329/jbs.v15i0.2209 J. bio-sci. 15: 99-109, 2007